Primary debulking surgery versus primary neoadjuvant chemotherapy for high grade advanced stage ovarian cancer - Kobal, Borut (Radiology and oncology (Ljubljana), 2018)
The aim of the study was to analyze the overall survival (OS) and progression free survival (PFS) of patients with high grade and advanced stage epithelial ovarian cancer (EOC) with at least 60 months of follow-up treated in a single gynecologic oncology institute. We compared primary debulking surgery (PDS) versus neoadjuvant chemotherapy plus interval debulking surgery (NACT + IDS) stratifying data based on residual disease with the intent to identify the rationale for therapeutic option decision and the role of laparoscopic evaluation of resectability for that intention. Patients and methods. This is observational retrospective study on consecutive patients with diagnosis of high grade and International Federation of Gynecology and Obstetrics (FIGO) stage III/IV EOC referred to our center between January 2008 and May 2012. We selected only patients with a follow-up of at least 60 months. Primary endpoint was to compare PDS versus NACT + IDS in term of progression free survival (PFS) and overall survival (OS). Secondary endpoints were PFS and OS stratifying data according to residual disease after surgery in patients receiving PDS versus NACT + IDS. Finally, through Cox hazards models, we tested the prognostic value of different variables (patient age at diagnosis, residual disease after debulking, American Society of Anesthesiologists (ASA) stage, number of adjuvantchemotherapy cycles) for predicting OS. Results. A total number of 157 patients were included in data analysis. Comparing PDS arm (108 patients) and NACT + IDS arm (49 patients) we found no significant differences in term of OS (41.3 versus 34.5 months, respectively) and PFS (17.3 versus 18.3 months, respectively). According to residual disease we found no significant differences in term of OS between NACT + IDS patients with residual disease = 0 and PDS patients with residual disease = 0 or residual disease = 1, as well as no significant differences in PFS were found comparing NACT + IDS patients with residual disease = 0 and PDS patients with residual disease = 0; contrarily, median PFS resulted significantly lower in PDS patients receiving optimal debulking (residual disease = 1) in comparison to NACT + IDS patients receiving complete debulking (residual disease = 0). PDS arm was affected by a significant higher rate of severe post-operative complications (grade 3 and 4). Diagnostic laparoscopy before surgery was significantly associated with complete debulking. Conclusions. We confirm previous findings concerning the non-superiority of NACT + IDS compared to PDS for the treatment of EOC, even if NACT + IDS treatment was associated with significant lower rate of post-operative complications. On the other hand, selecting patients for NACT + IDS, based on laparoscopic evaluation of resectabilty prolongs the PFS and does not worse the OS compared to the patients not completely debulked with PDS.
Keywords: epitelijski rak; intervalna citoredukcijska operacija; jajčniki; preživetje; primarna citoredukcijska operacija; rak (medicina); zdravljenje